The Impact of Video Streaming on Quality of Experience over 802.11n Dual Band networks: Experimental Evaluation - Bruzgiene, R.; Narbutaite, L.; Adomkus, T.; Cibulskis, R. (Elektronika ir Elektrotechnika, 2014)
Today’s users can access even video broadcasting services, however, video streaming over wireless networks is especially difficult due to the factors, influencing the wireless communication process: the signal strength, the interference from other wireless links and so on. So it is very important to analyze the parameters of video streaming over 802.11 wireless networks, evaluating the influence of different frequency bands on the characteristics of video Quality of Experience: Mean Opinion Score, Peak Signal to Noise Ratio and others. The experimental investigations of video streaming over 802.11n wireless network, which operates in simultaneous 2.4 GHz and 5 GHz frequency bands, are presented in this paper. The experimental investigations showed that there is big impact of the video multicast streaming on Quality of Experience characteristics over dual band wireless network. Due to this, the authors recommended the approach for the equipment of video streaming over 802.11n dual band wireless network, according to the analysis of experimental results and the existing wireless streaming problems in the network. DOI: http://dx.doi.org/10.5755/j01.eee.20.6.7291